Antimicrobial use in beef feedyard cattle in the United States - Hope, Katie Jo (Kansas State University, 2019)
Antimicrobial use is a common occurrence in modern food-animal production. These medications are utilized to prevent, control, and treat a wide variety of infectious diseases in beef cattle. However, as concerns related to antimicrobial resistant bacteria in human and animal health have mounted, countries throughout the world are measuring and monitoring antimicrobial use. These measurements are based on antimicrobial use metrics which generally consist of both a numerator (e.g., weight of product sold or used, number of animals exposed) and a denominator (e.g., animal population, time). This dissertation is focused on capturing, standardizing, and characterizing antimicrobial use data from 22 beef feedyards in the United States. Data management required navigation of challenges including feedyard recruitment, data acquisition across multiple record-keeping systems, data standardization, and analysis. These 22 feedyards sold a total of approximately 1.2 million head of beef cattle during 2016 and 2017. During their time in the feedyards, these cattle received 1,844,483 regimens of medically important antimicrobials across the categories of in-feed use, control of bovine respiratory disease, and individual animal therapy. Total antimicrobial regimens of medically important antimicrobials per animal year reported at the study level were 3.66 and 3.16 for 2016 and 2017, respectively. When these regimens are reported by use category; in-feed use contributed 2.90 for 2016 and 2.47 for 2017, control of BRD contributed 0.51 for 2016 and 0.40 for 2017, and individual animal treatment contributed 0.25 for 2016 and 0.29 for 2017. Total milligrams of medically important antimicrobials per kilogram liveweight produced were 44.92 and 32.45 for 2016 and 2017, respectively. All uses of non-medically important antimicrobials were in the feed; these uses reported as regimens per animal year were 2.81 in 2016 and 2.71 in 2017. Non-medically important antimicrobial use reported as total milligrams per kilogram liveweight produced were 95.88 and 85.42 for 2016 and 2017, respectively. To increase granularity, outcome values are also described by study year, use type (in-feed, control of bovine respiratory disease, and individual animal treatment), and antimicrobial class. This level of detail is necessary for interpretation at the individual feedyard level. Eighteen of the 22 feedyards also participated in a survey regarding their overall antimicrobial use. The survey results were compared to use estimates from the collected data for the year in which the survey was administered. Estimates of medically important antimicrobial regimens per animal year were 3.69 from survey results, compared to 3.62 from the record systems. Milligrams of medically important antimicrobials per kilogram liveweight produced were estimated as 49.10 from the surveys and 37.49 from the collected data. Estimates of time and resources for completing the project were kept to allow projection of required resources for expansion of the feedyard database. A total of 842 hours were required for data entry, standardization, analysis, and report preparation. Each additional feedyard would require approximately 1.4 days of travel time covering 474 miles and a per diem and lodging cost of $167 per feedyard. Travel time and cost may increase depending on recruitment challenges. The time needed for data management including data import, standardization, and quality control varies between eight and fifteen hours per feedyard depending on record-keeping system. The question of the application of antimicrobial use metrics related to antimicrobial resistance selection is key. To provide an example, a study was performed using known doses of chlortetracycline in mineral given orally in order to determine related changes in the presence and enumeration of selected antimicrobial resistance genes in fecal samples. The effect of antimicrobial treatment varied across different resistance genes with time and treatment-related trends.
Keywords: Antimicrobial use; Cattle; Feedyard; Metrics